Re-evaluation of DNA based identification results of victims of a terrorist attack 25 years later. Issue 1 (December 2019) - Corach, D.; Vullo, C.; Sala, A.; Catelli, M.; Caputo, M.; Romero, M.; Ginart, S.; Garrigós, L.; Fonderbrider, L.; Somigliana, C.
Abstract: In July 1994 there was a second terrorist attack against a Jewish institution in Buenos Aires city. It targeted the Argentine Israelite Mutual Association (AMIA) and the bomb toppled its building, killed 85 and hurt over 300 people. The Supreme Court ordered DFPS/SHDG to carry out the identification of the fragmented remains by means of DNA analysis. At that time five VNTRs, seven STRs including five autosomal, one X, and one on the Y chromosome, mtDNA sequencing (HVR I and II) and MVR were used. The techniques used were all manual, southern blot and polyacrylamide gels with radioactive probes or primer detection. The first report was presented on November 7, 1994. In addition to the molecular data, identifications were made using conventional forensic criteria: dactyloscopy, radiography, dentistry and personal traits. In July 2016, the AMIA Investigative Investigation Unit wanted to clarify the identity of additional victims and asked the DFPS/SHDG and as a second opinion laboratory the Argentine team of Forensic Anthropology (EAAF), to analyze samples in parallel, compare them to the results reported in 1994, and perform additional tests on samples not previously analyzed by DNA typing. Both laboratories used automated platforms (ABI 3500); commercial kits Powerplex Fusion, Identifiler and mtDNA sequencing. Although TH01 and vWA are the only tested STR markers in 1994 that are still in use, most results reported in 1994 were confirmed by both laboratories. Additionally, it was possible to identify a victim whose material had initially been analyzed but, given its state of degradation, it had not been possible to obtain a genetic profile. The use of more sensitive megaplexes made it possible to identify a missing person 23 years later. The overall results demonstrate the robustness of the DNA analyses and the great increase in the sensitivity of the new analytical systems used and underscore the importance of including a second opinion lab to warrant the quality of the results.